Experimental investigation on thermophysical properties of solar glycol dispersed with multi-walled carbon nanotubes. Issue 10 (2nd October 2016) - Kumar, P. Ganesh; Kumaresan, V.; Velraj, R.
ABSTRACT: This article deals with well-dispersed solar glycol-based nanofluids containing multi-walled carbon nanotube (MWCNT) nanoparticles with different particle volume concentrations of 0.1%, 0.2%, 0.3%, and 0.4% prepared by typical two-step method. Thermal conductivity, viscosity and specific heat capacity of solar glycol (SG)-based MWCNT nanofluids, in the temperature range of 30°C–70°C were measured. The values of density showed a noticeable deviation from the predictions of Pak and Cho correlation. Hence, correlations are developed for thermal conductivity and viscosity from the experimental results obtained from the various range parameters of interest. The presence of MWCNT enhanced the thermal conductivity of the nanofluids by 17.26% at 0.4 vol.% particle concentration at 70°C. The relative viscosity of MWCNT nanofluids depends on the nanoparticles percentage concentration and decreases significantly with increase in temperature for higher concentrations. The presence of MWCNT enhances the specific heat of the nanofluids significantly, and this enrichment decreases with the increase of the MWCNT concentration. MWCNT/SG represents a new and innovative class of heat-transfer fluid, which possesses excellent thermophysical properties. The MWCNT/SG-based nanofluids could be suitable working fluids for solar thermal and automobile applications.